Validasi Panjang dan Durasi Kemacetan Google Traffic dengan Survei Lapangan Pada Kasus Putaran Balik di Jl. Kol. H. Burlian Palembang - Syifa' Ul Haq; Ramadhani Ramadhani; Pujiono Pujiono (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Traffic congestion is one of the common problems in big cities such as Palembang, particularly at U-turn locations which are prone to bottlenecks. This study aims to validate the congestion length and duration data obtained from Google Traffic with direct field survey observations at the U-turn on Jl. Kol. H. Burlian, Palembang. The research method involved primary data collection through field surveys using a Garmin GPS to record congestion length and a Speed Gun to measure vehicle speed. Secondary data were obtained from Google Traffic, processed through Google Sheets and the Google Distance Matrix API. The results showed that Google Traffic data can generally illustrate the congestion patterns, both in terms of queue length and congestion duration. A paired t-test comparison between Google Traffic data and field survey data indicated no significant difference. Therefore, Google Traffic can be utilized as supporting data in congestion mapping, although field validation is still required for more accurate results.